Beliefs as a Means of Self-Control? Evidence from a Dynamic Student Survey - Felix Bönisch; Tobias König; Sebastian Schweighofer-Kodritsch; Georg Weizsäcker (Center for Economic Studies and ifo Institute (CESifo), 2024)
We repeatedly elicit beliefs about the returns to study effort, in a large university course. A behavioral model of quasi-hyperbolic discounting and malleable beliefs predicts that the dynamics of beliefs mirrors the importance of exerting self-control, such that believed returns increase as the exam approaches, and drop post-exam. Exploiting variation in exam timing to control for common information shocks, we find this prediction confirmed: average believed study returns increase by about 20% over the period before the exam, and drop by about the same afterwards. Additional analyses further support the hypothesized mechanism that beliefs serve as a means of self-control.
Keywords: C81; D81; D91; 330; beliefs; present bias; self-control; effort; survey